Visitor Perception of the Degradation of Bar Reef Kalpitiya Sri Lanka - JAYARATNE, Chamathi; WATTAGE, Premachandra; GUNAWARDENA, Prasanthi (Journal of Environmental Management and Tourism, 2024)
Bar Reef is a complex marine ecosystem with over 120 coral species living in the reef and over 300 fish species reported from the surrounding sea. It was declared a marine sanctuary in 1992. Despite efforts for conservation, the Bar Reef ecosystem is at risk of degradation due to overexploitation of extractive uses, namely, edible fish, other seafood species, and aquarium fish. In addition, destructive fishing practices are also responsible for damaging the reef ecosystem. The designation of Kalpitiya as a significant tourism promotion area has created additional pressure on the system. Further, the worldwide incidence of coral bleaching in 1998 has severely affected a major part of the Bar Reef. However, the amount of degradation persistent in the bar reef has not been valued so far. This research has attempted to value the extent of degradation prevailing in the Bar Reef from the perception of the visitors. It has used Choice Experiment Method to assess the visitors’ perception of the degradation. Randomly selected 250 visitors were interviewed and the conditional logit model has been used to investigate the visitor preferences towards the habitat quality and analyze the significance of their preferences. According to the results obtained reduction of plastic and polythene by 50%, reducing the crowding in the beach area by 15%, and paying Rs. 1000 has become significant. Hence it is expected by this research to provide a signal to the relevant stakeholders on the extent of degradation prevailing and the importance of protecting this habitat.